The A Phenomenological Perspective on the Perceptual World of Motorically Differently Abled Indonesian Authors in Their Novels - I Made Astika; Faruk Faruk; Pujiharto Pujiharto (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
The lives of differently abled individuals have long been overshadowed by stereotypes imposed by the non-disabled majority. As a result, their bodies are often perceived as incapable of engaging with the world meaningfully. However, narratives written by motorically differently abled authors demonstrate that they do not lose the capacity to make sense of reality. Rather, their perceptual experiences are constituted in different ways. Despite this, the nature of their perceptual world remains underexplored. This study aims to describe the perceptual world of motorically differently abled authors as represented in their novels. This study is limited to three novels by motorically differently abled authors and does not include other types of disabilities or non-literary texts. The data sources consist of Kau Begitu Sempurna by Ariny Nurul Haq, Om by Agil Rizkiani, and Menjeda Cinta by Indah Tinumbia. Drawing on three key concepts from Maurice Merleau-Ponty’s phenomenology of perception: chiasm, body schema, and intentionality, the data were analyzed using the Interpretative Phenomenological Analysis (IPA) method. The findings reveal that the perceptual world of motorically differently abled authors is constituted through three interrelated moments. First, chiasm shows how the differently abled body is “disabled” through the social gaze while also serving as a site for the reversal of stigma. Second, the body schema is extensive and plastic, integrating assistive devices and habitual movements as meaningful extensions of the body. Third, intentionality remains existentially oriented toward achievement, love, and meaningful existence, becoming more contemplative in embodied experience. The findings challenge normate-centered interpretations of disability and reposition differently abled authors as epistemic subjects in Indonesian literary discourse, demonstrating that their perceptual world is structured through embodied meaning-making with implications for disability, literature, and social inclusion.